Bipolar disorder: etiological, clinical and therapeutic challenges (Research, Society and Development, 2022)
Bipolar Disorder is a psychiatric condition characterized by severe mood swings between the opposite poles of affective experience, involving periods of high mood and depression, interspersed with periods of remission. A literature review was carried out, which sought to highlight the main etiologies of bipolar disorder, as well as the clinical and therapeutic challenges of approach. It was seen that bipolar disorder has a multifactorial, complex and broad etiology, directly related to neurochemical changes, cellular resilience and neuroplasticity, mitochondrial disorders and chronic stress and the inflammatory character. The average age at the onset of the disorder is 25 years, but it is very common in adolescence, with an increased frequency among women. In many cases, affected people are not diagnosed until 10 years after the onset of symptoms. Also, due to the variety of etiologies and clinical profiles, the therapy for the treatment and control of bipolar disorder is based on the use of neurotransmitter regulators, anticonvulsants, as well as maintaining adequate levels of lithium in the body. In addition, after the therapy is implemented, factors such as reduced social and family support, discredit to pharmacological therapy and traditional health care culminate in low therapeutic adherence and worsening of the condition.